2013
DOI: 10.1617/s11527-013-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Wheel tracking rutting performance estimation based on bitumen Low Shear Viscosity (LSV), loading and temperature conditions

Abstract: The development of new technologies and road pavement materials require the evaluation of the asphalt mixture performance. Rutting is one of the main modes of failure of asphalt mixtures; it is typically studied at the laboratory through the wheel tracking test (WTT). Weather and traffic conditions (temperature, loads) significantly affect the pavement rutting performance. The bitumen rheological properties also have a main role in mixture rutting response; they can adequately characterized by the bitumen Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Recently, the Rr limit of Agnusdei et al was verified considering the rheological properties of the binder such as low shear viscosity (LSV) in Morea et al [4,5]. In this work, drastic increases in Rr were observed when the original bitumen LSV was lower than 500 Pa.s at the same temperature as that of the WTT.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…Recently, the Rr limit of Agnusdei et al was verified considering the rheological properties of the binder such as low shear viscosity (LSV) in Morea et al [4,5]. In this work, drastic increases in Rr were observed when the original bitumen LSV was lower than 500 Pa.s at the same temperature as that of the WTT.…”
Section: Introductionsupporting
confidence: 57%
“…Furthermore, it was found that the mixtures studied showed drastic changes in rutting resistance when the asphalt binder achieved LSV values lower than 500 Pa.s. On the other hand, Morea et al [5] reported that the Rr value of 5 lm/min seems to be a turning point for rutting performance. This Rr threshold is related to the 500 Pa.s of the LSV limit.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is because the extrapolated curve may not present a plateau at very low frequencies but can be curvilinear in many cases. Thus, the common practice for studying PMB is to determine the LSV at a relatively low frequency instead [48][49][50], for example at 0.001 Hz (approximately 0.006 rad/s), which was used in previous studies [30,31].…”
Section: Low Shear Viscositymentioning
confidence: 99%